Fluid flow behavior and solidification process of welding pool under rapid cooling condition based on cellular automata‐lattice Boltzmann method (CA‐LBM) couple model. Issue 7 (20th July 2020) - Shi, F.; Zheng, Z.T.; He, M.; Lei, Y.F.; Guo, D.H.; Yu, J.L.
Abstract: Based on the basic principle of lattice Boltzmann method (LBM), this paper first establishes a numerical model for simulating the evolution process of flow field, temperature field and concentration field. Then the cellular automata‐lattice Boltzmann method (CA‐LBM) coupling model is established to simulate the solidification process of welding pool. Finally, the solidification process of the welding pool under different rapid cooling powers is analyzed. It is found that the solidification process of the welding pool is significantly correlated with the magnitude of the rapid cooling power. As the rapid cooling power increases, the maximum temperature, the temperature interval and the size of the welding pool decrease, which lead to the Marangoni convection effect in the welding pool increases obviously and the unevenness of the concentration field is reduced. Meanwhile, due to the increase in the degree of supercooling, the nucleation rate increases. Finally, under the combined action, the microstructure of the weld is refined. The results of the coupling model accurately reflect the complex changes of the physical fields in the solidification process of welding pool under different cooling power. It lays a foundation for solving practical engineering problems in large calculation area. Abstract : The cellular automata‐lattice Boltzmann method coupling model is established to simulate the solidification process of welding pool. When the rapid cooling power is increased to 500 W, the grains are significantly refined and the more equiaxed grains are formed in the weld. Coupling model more accurately simulates the effect of rapid cooling power on the solidification process of the weld pool.